Management of Root Knot Nematode on Tomato through Grafting Root Stock of Solanum sisymbriifolium - Baidya, Suraj; Timila, Ram Devi; KC, Ram Bahadur; Manandhar, Hira Kaji; Manandhar, Chetana (Journal of Nepal Agricultural Research Council, 2017)
The root-knot nematodes (Meloidogyne spp) are difficult to manage once established in the field because of their wide host range, and soil-borne nature. Thus, the aim of the present study was to examine the use of resistant root stock of wild brinjal (Solanum sisymbriifolium) to reduce the loss caused by the nematodes on tomato. For the management of root-knot nematodes, grafted plant with resistant root stock of the wild brinjal was tested under farmers’ field conditions at Hemza of Kaski district. Grafted and non-grafted plants were produced in root-knot nematode-free soil. Around three week-old grafted and non-grafted tomato plants were transplanted in four different plastic tunnels where root-knot nematodes had been reported previously. The plants were planted in diagonal position to each other as a pair plot in 80 × 60 cm2 spacing in an average of 20 × 7 m2 plastic tunnels. Galling Index (GI) was recorded three times in five randomly selected plants in each plot at 60 days intervals. The first observation was recorded two months after transplanting. Total fruit yield was recorded from same plants. In the grafted plants, the root system was totally free from gall whereas in an average of 7.5 GI in 0-10 scale was recorded in the non-grafted plants. Fruits were harvested from time to time and cumulated after final harvest to calculate the total fruit yield. It was estimated that on an average tomato fruit yield was significantly (P>0.05) increased by 37 percent in the grafted plants compared with the non-grafted plants. Grafting technology could be used effectively for cultivation of commonly grown varieties, which are susceptible to root-knot nematodes in disease prone areas. This can be used as an alternative technology for reducing the use of hazardous pesticides for enhancing commercial organic tomato production. Journal of Nepal Agricultural Research Council Vol.3 2017: 27-31